Mykola lavrovskyi – the first director of nizhyn institute оf history & philology - Mytsyk, L. M. (Видавництво НДУ ім. Миколи Гоголя, 2018)
The task of this paper is an attempt to systematize the documentary and factual material on the figure of Mykola Lavrovskyi introduced into the scientific circulation and determine his role in the history of Nizhyn. The author proves that Mykola Lavrovskyi has brilliantly coped with the task set before him – the creation of a higher educational institution of a new type for training teachers in Nizhyn in 1875, – revealing the outstanding qualities of the administrator, the economist, the teacher, and the scholar.
Keywords: Nizhyn Institute of History & Philology; Nizhyn Gimnasia of Higher Sciences; learning, internship